Adult learning practises during a time of organisational change: implementing the SAP R/3 computer system at a university - Pieters, Elaine (School of Education, 2024)
The research is an attempt to understand adult learning practices in an organisation that is undergoing significant change in its financial practices. This change has brought with it a new computer system in the form of SAP R/3. A case study was used, namely the implementation of SAP R/3 at the University of Cape Town (UCT). The system was implemented by the PRISM Project, whose training team delivered most of the formal training that was required. The researcher is a member of this training team. Four areas of research theory are used to analyse the case. A theory of organisational change is used to assess organisational learning. A model of adult learning is used to assess adult learning practices. It highlights three elements namely the learner and what they bring to the learning-teaching situation, the task and what it demands, and the means to build a bridge between the two. Theories of adult cognition are used to illuminate this model. Finally, role and discourse theory is used to understand how adults interact with others and approach the role of learner. A qualitative research methodology was used. Thirty adults, "end users" from various levels and areas of the organisation were interviewed. I also interviewed PRISM Project Managers, trainers and representatives of central administrative departments. The data was coded and analysed, and provided a rich source of contextual data that described adult's experiences of learning to use SAP R/3 and of coping with organisational change. The research was concerned with answering two main questions: Firstly, What organisational learning took place? Including what new organisational norms adults needed to learn about and what the organisation's theory in use of finances and SAP R/3 was. Secondly, using the adult learning model, What adult learning practices were found at UCT? I was particularly interested in the effect of role and discourse brought to learning, and in classifying different strands of the learning task and assessing which mediators of learning worked best for each. The research findings address these issues and I conclude with some implications for practice.